6x-3(5x+2)=4-5x

Simple and best practice solution for 6x-3(5x+2)=4-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3(5x+2)=4-5x equation:


Simplifying
6x + -3(5x + 2) = 4 + -5x

Reorder the terms:
6x + -3(2 + 5x) = 4 + -5x
6x + (2 * -3 + 5x * -3) = 4 + -5x
6x + (-6 + -15x) = 4 + -5x

Reorder the terms:
-6 + 6x + -15x = 4 + -5x

Combine like terms: 6x + -15x = -9x
-6 + -9x = 4 + -5x

Solving
-6 + -9x = 4 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-6 + -9x + 5x = 4 + -5x + 5x

Combine like terms: -9x + 5x = -4x
-6 + -4x = 4 + -5x + 5x

Combine like terms: -5x + 5x = 0
-6 + -4x = 4 + 0
-6 + -4x = 4

Add '6' to each side of the equation.
-6 + 6 + -4x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -4x = 4 + 6
-4x = 4 + 6

Combine like terms: 4 + 6 = 10
-4x = 10

Divide each side by '-4'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 5.2x(2x+4)=30 | | 7x+24=-4 | | 5.2x+4=30 | | (8-17)+3= | | 6b-(b-3)=56 | | (8x-17)+3= | | k+2k=65 | | 252+4x=284 | | 2y/y-1=5/y+(10-8y)/(y^2-y) | | 5i/(6-2i) | | 37-n=12 | | -18=-3z | | 2x+4+3x=24 | | 12x+25=200 | | 12+n=17 | | 180-x=3(x-2) | | 11+5=16 | | -3/8-(-1/5)-(-7/3) | | 3(-2+3n)=-7n-6 | | -4y=4 | | -7(a+5)=-40-8a | | -36-7x=6(4-4x)+5x | | 4-8x=5(4x+6)-2x | | 10+n/15=12 | | 12+3y=84 | | -62=5-3(1-3x) | | 4+5(8+6m)=-22+8m | | 24+2x=2(2x+7) | | 5x^3+15x^2+12x+36=0 | | 1-8(5k-5)=-33-3k | | -3-3b=-(-2+4b) | | 8/5-2=-13 |

Equations solver categories